Detective daddy - Kane, Mallory; Copyright Paperback Collection (Library of Congress) (Toronto ; New York : Harlequin, 2011)
"He learned he was going to be a daddy the same day his parents' murderer was set free. But Detective Ash Kendall was determined to keep it together. After all, one woman was at the center of everything, and Rachel Stevens had a lot of explaining to do. The lovely DNA profiler had no idea her evidence would reopen Ash's old wounds. Despite all they'd been through, she hadn't stopped loving the man who just found out he was going to be a daddy. And with someone desperate to keep the secrets of the Christmas Eve murders hidden, Ash was the only man who could protect Rachel and her baby"--Publisher.
Keywords: Police -- Fiction; Forensic scientists -- Fiction; Pregnant women -- Fiction; Murder -- Investigation -- Fiction; Romantic suspense fiction; Christmas stories